PERANAN GURU FIQIH DALAM MENUNTUN SISWA PADA PRAKTIK SHOLAT DI MADRASAH IBTIDAIYAH - Ali Muddin Jailani (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2024)
This study examines the role of Fiqh teachers in guiding students in prayer practice at Madrasah Ibtidaiyah. As a mandatory worship for every Muslim, prayer needs to be taught from an early age so that it becomes part of daily habits. Fiqh teachers have the main responsibility in conveying theoretical understanding and guiding students in prayer practice. This study uses a qualitative method with a descriptive approach, where data is obtained through observation, interviews, and documentation. The results showed that 85% of Fiqh teachers have conveyed the theory of prayer well, while 70% of teachers are actively guiding students in hands-on practice. Evaluation of the implementation of prayer is carried out by 75% of teachers, but only 60% of students are able to carry out prayer movements correctly without errors. Some of the obstacles faced in prayer learning include lack of student attention (40%), limited learning time (65%), and lack of supporting facilities (55%). To overcome these obstacles, teachers apply various strategies such as demonstration methods, congregational prayer habits, and the use of interactive learning media. With the right strategy, the effectiveness of prayer learning can increase and have a positive influence on the spiritual development and character of students